An Analysis of Students' Reading Interest towards Short Stories of Nias at the Eighth Grade of SMP Negeri 4 Namohalu Esiwa - Ester Zebua; Elwin Piarawan Zebua; Kristof Martin Efori Telaumbanua; Riswan Zega (Journey: Journal of English Language and Pedagogy, 2024)
This research aims to analyze students’ reading interest by using short stories of Nias and factors that influenced their reading interest at the Eighth Grade of SMP Negeri 4 Namohalu Esiwa. To conduct this research, the researcher used qualitative research with an ethnographic approach. The use of qualitative research with an ethnographic approach can be a valuable method for conducting this study. The researcher shared Nias short story book with the students’ and gave them time during the week to read, and data was collected through a questionnaire and an interview. The data was analyzed using the technique of the Miles and Huberman Theory Framework. Based on the questionnaire, the result showed that the average students’ reading interest in short stories of Nias got 76.5% in the high category. The result obtained from the sixth indicator of reading interest towards short stories of Nias (needs of reading, action to search for reading matter, reading amusement, interest in reading, desire to read, and follow-up). Based on the results of the interview, students’ reading interest towards short stories of Nias influenced by internal and external factors. An internal factor is motivation. External factors are book design and book content, environment, language, and the internet (network).